Notes on Q-Intuitionistic Fuzzy Subsemiring of a Semiring - Vanathi, K; Subramanian, V.S.A; Arjunan, K (International Journal of Mathematical Research, 2014)
In this paper, we make an attempt to study the algebraic nature of Q-intuitionistic fuzzy subsemiring of a semiring and some properties of Q-intuitionistic fuzzy subsemiring of a semiring are investigated. AMS Mathematics Subject Classification (2010): 06D72, 08A72, 03F55.